The effect of macroeconomic variables on public debt in ASEAN countries / Nurfazilah Wahadiah Abdurahman - Abdurahman, Nurfazilah Wahadiah (2019)
This study analyzed the relationship of Public debt on macroeconomics variables and it showed how those factors affecting the public debt. This study investigates the effect of public debt on Macroeconomics variables in Eight ASEAN countries which is Malaysia, Indonesia, Thailand, Vietnam, Singapore, Brunei, Philippines, and Myanmar. The data collected from 2004 to 2018 and the macroeconomics variables are Gross Domestic Product (GDP), Foreign direct investment, Inflation Rate, Trade Openness, and Inflation on the public debt in ASEAN countries. Next, method is use in these studies diagnostic testing, panel unit root testing, multicollinearity, heteroskedasticity and autocorrelation test. While, result of Hausman Test we choose fixed effect model the appropriate panel data estimator for baseline model. In addition, Results obtained from this research shows that trade openness and inflation are highly significant and negative relationship on public debt while other variables which is foreign direct investment, gross domestic product and interest rate are not significant but has positive effect on public debt.